Economic performance of production of Croatian cheese ripened in a lamb skin sack (Sir iz mišine) - Blažević, Lovorka (Array, 2020)
Cheeses matured in skin sack is traditionally produced in several Mediterranean countries, which in Croatia has been retained in the territory of Dalmatian hinterland. The characteristic of this cheese is its piquant flavour and aroma, as a consequence of ripening in anaerobic conditions in lamb skin. This type of cheese has been recognized and has its customers in the wider area of the Croatia, and it is an interesting touristic product. The major constraint is that the production of this type of cheese in Croatia has been reduced to sporadic production in several families that preserve the tradition of their ancestors and the produced quantities are insufficient to meet customers needs. In 2009, Dalmatian hinterland had 11 registered producers of this type of cheese, while there are currently only 2. A production and economic analysis was performed of the remaining producers in order to determine the production performance. Both family farms produce cheese from sheep milk, while the first farm owns 300 sheep and the second 500. The selling price of cheese reaches HRK 150 per kilo, which ensures the achievement of cost-effectiveness of production. The producers point out that all the produced quantity is sold to known customers through on-farm sales and the demand exceeds the supply. Such a product would arise extreme interest among tourists, while the basic prerequisite for that is increase of the annual production of cheese by increase of the number of producers, as well as their clustering and protection of the product by one of the quality marks at the EU level.